(untitled) (De Rebus Antiquis, 2021)
This article delves into the relevance of the concept of “total war” as it is applied to the Peloponnesian War. In so doing, it is noticed a lack of consensus among contemporary scholar in regards to what is required for a war to be considered as total. Therefore, I here advance three sufficient and necessary conditions to deem a warlike conflict as total war. My conclusion, on the one hand, is that the Peloponnesian War fulfilled only part of those conditions. On the other, I hold that the tendency among Hellenists is to constantly compare the two World Wars that ravaged the 20th-century. This distorts the analysis and hampers the explanatory capacity of the concept.